DAMPAK SOSIAL PERUSAHAN HARITA GROUP TERHADAP MINAT PENDIDIKAN GENERASI MUDA STUDI KASUS DI DESA SOLIGI KECAMATAN OBI SELATAN HALMAHERA SELATAN - Sampela, Trisani; Djumat, Irwan; Kamisi, Mohtar; Misrina, Misrina (Universitas Khairun, 2025)
This study aims to: analyze the Social Impact of Harita Group Company on the Educational Interest of the Young Generation in Soligi Village, to find out and map the Supporting and Inhibiting Factors of Harita Group Company on the Educational Interest of the Young Generation Case Study in Soligi Village. The research method used is qualitative research with a case study approach and sampling purpose. The results of the study show that: The Social Impact of Harita Group Company on the Education of the Young Generation in Soligi Village, South Obi District, South Halmahera, has a very bad impact on the future of the young generation in Soligi Village.